AB0530 CHARACTERISTICS AND MEDIUM-TERM OUTCOMES OF TAKAYASU ARTERITIS–RELATED RENAL ARTERY STENOSIS: ANALYSIS OF A LARGE CHINESE COHORT. (2nd June 2020) - Sun, Y.; Dai, X.; LV, P.; Dong, Z.; Lin, J.; Jiang, L.
Abstract : Background: The incidence of renal artery stenosis in Takayasu arteritis (TA) was 20%–60% according to previous reports. The specific characteristics of patients with TA-related renal artery stenosis and the effect of revascularization procedures on prognosis have not been fully investigated. Objectives: To investigate the characteristics of patients with TA-related renal artery stenosis and identify the predictors of medium-term adverse outcomes. Methods: Data for 567 patients registered in a large prospective observational cohort-the East China Takayasu arteritis cohort-up to April 30, 2019, were retrospectively analyzed. Results: Renal artery stenosis was confirmed in 172/567 (30.34%) patients, with left renal artery involvement seen in 73/172 (42.44%) patients. Renal insufficiency at presentation (HR = 2.37, 95% CI: 1.76-15.83, p = 0.03), bilateral renal artery involvement (HR = 6.95, 95% CI: 1.18-21.55, p = 0.01), and severe (>75%) stenosis (HR = 4.75, 95% CI 1.08-11.33, p = 0.05) were predictors of adverse outcomes. Revascularization was performed for 46/172 (26.74%) patients. Patients without preoperative treatment had higher rate of restenosis (44.44% vs. 15.79%, p < 0.01) and hypertension deterioration (25.93% vs. 10.53%, p < 0.01) after the procedure. Non-receipt of preoperative treatment (HR = 6.5, 95% CI: 1.77-32.98, p = 0.04) and active disease at revascularization (HR = 4.21, 95% CI 2.01-21.44, p = 0.04) were independent predictors of adverse outcomes after revascularization. Conclusion: Patients with uncontrolled or worsening hypertension or/and renal function may benefit from revascularization. Those who have received preoperative treatment may have more favorable revascularization outcomes. Prognosis appears to be poorer for patients with renal insufficiency at presentation, bilateral artery involvement, and severe stenosis. References: [1]Watanabe Y, Miyata T, Tanemoto K. Current clinical features of new patients with Takayasu arteritis observed from a cross-country research in Japan: age and sex specificity. Circulation 2015; 132: 1701-9. [2]Peng M, Jiang XJ, Dong H, et al. Etiology of renal artery stenosis in 2047 patients: a single-center retrospective analysis during a 15-year period in China. J Hum Hypertens 2016; 30: 124-8 Disclosure of Interests: None declared